Electronic medical records and biobanking - O. V. Kopylova; A. I. Ershova; I. A. Efimova; A. V. Blokhina; A. S. Limonova; A. L. Borisova; M. S. Pokrovskaya; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
Biosample preservation for future research is a fundamental component of translational medicine. At the same time, the value of stored biosamples is largely determined by the presence of related clinical data and other information. Electronic medical records are a unique source of a large amount of information received over a long period of time. In this regard, genetic and other types of data obtained from the biosample analysis can be associated with phenotypic and other types of information stored in electronic medical records, which pushes the boundaries in large-scale genetic research and improves healthcare. The aim of this review was to analyze the literature on the potential of combining electronic medical records and biobank databases in research and clinical practice.